The Advent of Spinoplastics: Easing the Growing Global Disease Burden of Spinal Injury - Delancy, Matthew M.; Perdanasari, Aurelia; Davis, Matthew J.; Abu-Ghname, Amjed; Kaplan, Jordan; Winocour, Sebastian J.; Reece, Edward M.; Sim, Alfred Sutrisno (Seminars in Plastic Surgery, 2021)
Epidemiologic studies have demonstrated a growing global disease burden of pathologies affecting the vertebral column. Allograft or implant-based reconstruction and fusion surgeries have been the mainstay of treatment. The efficacy of various surgical methods and the reliability of instrumentation or implants to execute these surgeries continue to be debated in the literature. Advances such as the free-tissue transfer have improved postoperative measures; however, they add high operative risk. The advent of spinoplastics introduces a practical surgical model to augment these spinal surgeries using vascularized bone grafts. As this technique becomes more widespread, it can be utilized to ease the growing disease burden that spinal injury places on both patients and the health care system. Ultimately, it will ameliorate strains on health care resources, reduce health care costs, and improve patient outcomes and quality of life.
Keywords: spinoplastics; disease burden; spinal reconstruction; spinal fusion; bone flap; vascularized bone graft